2005
DOI: 10.1211/ijpp.13.4.0001
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and acceptability of community pharmacy-based interventions in type 2 diabetes: a critical review of intervention design, pharmacist and patient perspectives

Abstract: Objective It is generally accepted that greater use could be made of community pharmacy‐based interventions. Diabetes care has been proposed as an area for enhanced community pharmacy involvement. However there is no published structured review of available evidence of either effectiveness or acceptability. This review aims to identify and assess such evidence and to synthesise findings to inform the design and delivery of future community pharmacy‐based interventions in diabetes care. Method A systematic sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…The authors' countries were obtained in order to verify the origin of the reviews. Seven of the authors were from the United States [6,[18][19][20][21][22][23][24] were from the United Kingdon [5,[25][26][27][28][29][30] were from Australia [3,5,[31][32][33][34] were from Canada [2,3,35,36] were from Switzerland [1,37,38] was from Spain [1,4] was from the Netherlands [38] and 1 was from Belgium [39]. The other 5 studies were multinational [40][41][42][43][44], with the authors originating from such countries as Australia, Brazil, Canada, Hong Kong and the UK.…”
Section: Resultsmentioning
confidence: 99%
“…The authors' countries were obtained in order to verify the origin of the reviews. Seven of the authors were from the United States [6,[18][19][20][21][22][23][24] were from the United Kingdon [5,[25][26][27][28][29][30] were from Australia [3,5,[31][32][33][34] were from Canada [2,3,35,36] were from Switzerland [1,37,38] was from Spain [1,4] was from the Netherlands [38] and 1 was from Belgium [39]. The other 5 studies were multinational [40][41][42][43][44], with the authors originating from such countries as Australia, Brazil, Canada, Hong Kong and the UK.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand. a review by Blenkinsopp and Hassey reported that there is limited evidence of the effectiveness of community pharmacy-based interventions in diabetes care [60].…”
Section: Factors Associated With Adherencementioning
confidence: 99%
“…However, the Norwegian Diabetes Association's requests for pharmacy services are described in the Norwegian diabetes declaration for pharmacies [15], see Box 1. Evidence as to the effectiveness of pharmacy involvement in diabetes care is at present not conclusive [16].…”
Section: Introductionmentioning
confidence: 99%